Imperial Laughs: A Soldier's Song and the Colonial Present - Wall, Tyler (Social justice, 2010)
The article offers observations and critiques of the song "Hadji Girl" written by U.S. Marine Corporal Joshua Belile during his deployment in the Iraq War. Details are provided about Belile's song that explains the murder of an Iraqi family after a U.S. soldier is invited to the home of an Iraqi girl. The author offers opinions about racial inversion, dehumanization, and objectification of women and Iraqis within the song. The responses of other U.S. soldiers to the content of the song are also discussed. It is suggested that the song has implications for the attitudes and views of U.S. soldiers towards Iraqis, violence, and death in the Iraq War.